2019
DOI: 10.1177/0890334419830988
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ Involvement in Their Wives’/Partners’ Breastfeeding: A Descriptive Correlational Study

Abstract: Background: Fathers’ involvement has been identified as a significant predictor in maternal breastfeeding outcomes. Its benefits have been well-documented, but limited studies have examined its influencing factors. Research aim: To investigate factors influencing fathers’ involvement in their partners’ breastfeeding. Methods: A descriptive correlational design was used. Data were collected from 151 fathers from four obstetrics wards of a public hospital in Singapore from October 2016 to December 2016. Self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…In our study, a stable relationship was associated with more extended periods of BF and was attributed to partner support of BF. This support has been previously associated with increased rates of initiation and duration of BF (Leng et al., 2019; Rempel et al., 2017).…”
Section: Discussionsupporting
confidence: 82%
“…In our study, a stable relationship was associated with more extended periods of BF and was attributed to partner support of BF. This support has been previously associated with increased rates of initiation and duration of BF (Leng et al., 2019; Rempel et al., 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Under these circumstances the fathers had no control over the situation as they were unable to step in and take over in order to help. One possible reason for feeling unable to support could be lack of knowledge about breastfeeding and how to support mothers in the best way possible [ 18 ]. A more effective approach would be for the fathers and staff to work together to find individual solutions to support the mothers with breastfeeding and breastmilk expression.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the father of an extremely preterm infant in the NICU may be influenced by the context, country of origin and personal preferences [ 17 ]. A recent study involving fathers of full-term infants from Singapore, showed that fathers’ involvement in breastfeeding was influenced by perceived approval of family members and friends, fathers’ knowledge of breastfeeding and marital relationships [ 18 ]. However, becoming a father to an extremely preterm infant hospitalised in a family-centred NICU for months provides a different perspective and context as the fathers are more involved in the care.…”
Section: Introductionmentioning
confidence: 99%
“…There is literature to suggest that other constructs may be important in their partner's breastfeeding behaviour, such as attitudes towards breastfeeding (Al Namir et al, 2017). The role of fathers' subjective norms in their partners' breastfeeding behaviour is sparse; however, there is some literature to suggest that fathers' subjective norms may influence their involvement in breastfeeding (Leng et al, 2019; Ng et al, 2019), demonstrating some potential for fathers' subjective norms to influence their partner's breastfeeding behaviour. Nonetheless, further research is needed to determine the role of fathers' subjective norms and their partner's breastfeeding behaviour.…”
Section: Discussionmentioning
confidence: 99%